Does bedtime music listening improve subjective sleep quality and next-morning well-being in young adults? A randomized cross-over trial - MAJEED, Nadyana M. (Institutional Knowledge at Singapore Management University, 2021)
Previous research has found that young adults exhibit patterns of poor sleep and that poor sleep is associated with a host of negative psychological consequences. One potential intervention to improve sleep quality is listening to music at bedtime. Although there exist previous works investigating the efficacy of listening to music as a form of sleep aid, these works have been hindered by statistically weak designs, a lack of systematic investigation of critical characteristics of music that may affect its efficacy, and limited generalizability. In light of the limitations in the existing literature, a 15-day randomized cross-over trial was carried out with 62 young adults. Participants completed 5 nights of bedtime listening in each condition (happy music vs. sad music vs. pink noise, which acted as an active control condition) over 3 weeks. Upon awakening each morning, participants rated their subjective sleep quality, current stress, positive and negative affective states, and current life satisfaction. Frequentist and Bayesian multilevel modeling revealed that happy and sad music were both beneficial for subjective sleep quality and next-morning well-being, compared with the pink noise condition; potential nuances are discussed. The current study bears potential practical applications for health-care professionals and lay individuals.